Padlet as Learning Media to Improve Students’ Writing Skills: EFL Teacher’s and Students’ Perspective - Novianto, Ahmad; Rohayati, Dedeh; Faridah, Didih (Journal of English Education Program (JEEP), 2024)
This study was designed to find out if there are significant differences in writing skills between students who are taught by means of Padlet and those who are not, and to find out the teacher’s and students’ perceptions of the implementation of Padlet in teaching writing. This mixed method study used quantitative data completed with a quasi-experimental pre-test and post-test control group design, and with a semi-structured interview for the qualitative data.  The study engaged 20 students as the experimental and control group. Based on the statistical data, after the teacher's treatment using Padlet on students' writing recount text, the t-observed value was higher than the t- table value. Thus, the null hypothesis (H0) was rejected and the alternative hypothesis (HI) was accepted. So, Padlet in the class on writing recount text reveals that there are differences in the improvement of students' abilities. Furthermore, the perceptions of teachers and students from the results of both interviews are of the notion that Padlet can improve writing skills, particularly in writing recount text. The finding showed that Padlet is effective as a media to improve students' writing skills. Some recommendations are addressed, particularly for the teacher and future research. Teachers are recommended to use the Padlet application as a media in teaching writing recount text and as one of the effective technology media. Since the present study only focus on mean differences in student improvement, the next researcher are expected to find out the significance of changes or differences in student achievement.